Therapeutic synergy and complementarity for ischemia/reperfusion injury: β1-adrenergic blockade and phosphodiesterase-3 inhibition. (1st July 2016) - Huang, Ming-He; Poh, Kian-Keong; Tan, Huay-Cheem; Welt, Frederick G.P.; Lui, Charles Y.
Abstract: The β1 -blocker when administered before reperfusion activates myocyte prosurvival signaling via β2 -adrenergic receptor (β2 -AR) and protein kinase A (PKA)-dependent mechanism during ischemia/reperfusion (I/R). The heart is endowed with powerful self-protective ability executed by endogenous β2 -adrenopeptide receptor activation. I/R triggers cardiac epinephrine and neuropeptide calcitonin gene-related peptide (CGRP) release. Cardiac β1 - and β2 -AR stimulation mediates pro- and anti-apoptotic cell signaling, respectively. Removal of myocardial β1 -AR-derived proapoptotic force with β1 -AR blockade unmasks the dominance of β2 -AR mediated prosurvival cell signaling through the well-defined PKA-Akt dependent mechanism. This review focuses on recent clinical and experimental findings including intrinsic cardiac β2 -adrenopeptide neuroparacrine signaling mechanisms involved in I/R injury protection. While β2 -adrenopeptide-mediated cardioprotection is important, age-related β2 -adrenopeptide receptor decoupling can result in their ineffectiveness in response to the receptor-specific therapies. Accordingly, direct activation of receptor-coupled upstream PKA-dependent signaling may serve as a therapeutic alternative to achieve cardioprotection bypassing adrenopeptidergic receptor decoupling accompanied with aging. Phosphodiesterase-3 (PDE3 ) inhibitor reduces infarct-size via cAMP-dependent PKA signaling. Non-β1 -AR-mediated PKA activation activates multiple prosurvival signaling pathways eventually leading to Akt activation. Combination therapy with β1 -blocker esmolol and PDE3 inhibitor milrinone additively reduced infarct-size in preclinical studies. Concurrent β1 -AR blockade and PDE3 inhibition provides complementary synergy with promising therapeutic potential in patients with acute myocardial infarction and beyond. Highlights: Cardiac β1 - and β2 -AR stimulation mediates pro- and anti-apoptotic cell signaling respectively. β1-AR blockade creates the dominance of β2 -AR-PKA-dependent infarct-size reduction. Enhanced cardiac epinephrine release from ICA cells activates β2 -AR-PKA dependent prosurvival signaling. Direct PKA activation with PDE3 inhibitor confers potent infarct-size reduction. Combination therapy with β-blocker and PDE3 inhibitor confers synergistic heart protection.